Probing the electronic states of high-TMR off-stoichiometric Co 2 MnSi thin films by hard x-ray photoelectron spectroscopy - Kozina, Xeniya; Karel, Julie; Ouardi, Siham; Chadov, Stanislav; Fecher, Gerhard H.; Felser, Claudia; Stryganyuk, Gregory; Balke, Benjamin; Ishikawa, Takayuki; Uemura, Tetsuya; Yamamoto, Masafumi; Ikenaga, Eiji; et al. (Physical Review B - Condensed Matter and Materials Physics, 2014)
The tunnel magnetoresistance ratio (TMR) of fully epitaxial magnetic tunnel junctions with an off-stoichiometric Co2MnSi Heusler alloy has been shown to exhibit a systematic dependence on Mn content, reaching 1135% at 4.2 K for Co2Mn1.29Si. In this paper, we explain the behavior of the observed TMR ratio using ab initio calculations and hard x-ray photoelectron spectroscopy (HAXPES). For the Mn-deficient samples, we show that the the drop of the TMR is caused by Co antisite atoms, which impose extra states into the minority-spin band gap. On the other hand, Mn-excess composition shows nearly half-metallic behavior. This result can be intuitively understood since both Co2MnSi and Mn2CoSi are theoretically predicted to be half-metallic ferromagnets. © 2014 American Physical Society.
CRIS-Team Scopus Importer:2023-03-20